Habitus in the Preservation of Traditional Dance Arts at the Semarak Candrakirana Art Center Dance Studio - Aida Choirunnisa*; Septina Galih Pudyastuti; Siany Indria Liestyasari (Universitas Syiah Kuala, 2024)
This research aims to find out the habituation of sanggar Candrakirana Semarak introduces traditional dance to the community and to find out how Sanggar Candrakirana Semarak preserves traditional dance. This research is qualitative with case study methodology. Administrators, trainers, students, archives of Candrakirana Semarak Studio, journals, and publications are the data sources of this research. Purposive sampling was used as the research sampling method. Data collection was done directly. This research approach uses source triangulation with interactive analysis methodology for data analysis. The following are the research findings. First, Semarak Candrakirana studio has a plan to preserve the art of dance, which includes the establishment of a training studio, participation in an event, dance preparation, and promotion on social media. The habit of Semarak Candrakirana studio is formed by the founders and trainers of the studio. There is capital that plays a role in maintaining the studio. Economic capital is obtained from dues and fees and performance fees. Social capital comes from the relationship between the founder and the trainers. Cultural capital comes from skills and education. Symbolic capital comes from the attractiveness of the studio. Sanggar Semarak Candrakirana is a place or training arena to preserve traditional dance in the city of Surakarta.